2017
DOI: 10.1038/s41598-017-03493-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of retinal pigment epithelial cell phenotype by Annexin A8

Abstract: The retinoic acid derivative fenretinide (FR) is capable of transdifferentiating cultured retinal pigment epithelial (RPE) cells towards a neuronal-like phenotype, but the underlying mechanisms are not understood. To identify genes involved in this process we performed a microarray analysis of RPE cells pre- and post-FR treatment, and observed a marked down-regulation of AnnexinA8 (AnxA8) in transdifferentiated cells. To determine whether AnxA8 plays a role in maintaining RPE cell phenotype we directly manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…The UPR principally acts to attenuate global translation via PERK and eif2α phosphorylation 23 . Previous studies have determined that PERK knockdown in mouse embryonic fibroblasts (MEF) results in increased 35 S -labeled cellular protein in the ER, indicative of an impaired attenuation of global translation and an increase of protein binding to GRP78 due to a loss of PERK kinase activity and eif2α phosphorylation 8 . In this context, our findings support the notion that upregulated GRP78 is an adaptive response intended on delaying induction of apoptotic pathways in ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The UPR principally acts to attenuate global translation via PERK and eif2α phosphorylation 23 . Previous studies have determined that PERK knockdown in mouse embryonic fibroblasts (MEF) results in increased 35 S -labeled cellular protein in the ER, indicative of an impaired attenuation of global translation and an increase of protein binding to GRP78 due to a loss of PERK kinase activity and eif2α phosphorylation 8 . In this context, our findings support the notion that upregulated GRP78 is an adaptive response intended on delaying induction of apoptotic pathways in ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…in culture and can be induced to transdifferentiate towards a neuronal-like phenotype upon certain stimuli 11,17 . We recently found that AnxA8 was down-regulated in ARPE-19 cells induced towards a neuronal lineage following treatment with FR, and showed that AnxA8 down-regulation is both necessary and sufficient for RPE transdifferentiation 13 . FR-induced AnxA8 loss also correlated with decreased expression of the Wnt-related genes Frizzled-1, Frizzled-4 and Wnt2b (Table 1), leading us to hypothesize that AnxA8 may regulate RPE phenotype via modulation of Wnt signaling.…”
Section: Fr and Anxa8 Loss Both Induce Neuronal Transdifferentiationmentioning
confidence: 99%
“…A microarray analysis performed on FR-transdifferentiated RPE cells revealed down-regulation of AnxA8 and suppression of several genes involved in Wnt signaling 13 , raising the question of whether cross-talk occurs between AnxA8 and Wnt signaling. Canonical Wnt signaling maintains cell fate specification and proliferation in diverse mammalian cell types 14,15 and it occurs upon binding of secreted Wnt proteins to Frizzled receptors and their co-receptors, lipoprotein receptor-related proteins (LRP)-5 and 6.…”
mentioning
confidence: 99%
“…49,50 Retinal pigment epithelium perform a variety of functions to support and protect the retina, including phagocytosis of the PR outer segments, adsorption of free radicals by pigment granules, and maintenance of ocular immune privilege by forming the outer blood-retina barrier. 51…”
Section: Retinal Pigment Epitheliummentioning
confidence: 99%